2002
DOI: 10.1046/j.1365-3059.2002.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in populations of the eyespot fungiTapesia yallundaeandT. acuformisunder different fungicide regimes in successive crops of winter wheat, 1984–2000

Abstract: Effects of regular treatments with the fungicides carbendazim and prochloraz applied to whole plots divided into subplots with different initial population mixtures of carbendazim-sensitive or carbendazim-resistant Tapesia yallundae or T. acuformis were studied in successive crops of winter wheat from 1984 / 85 to 1999 / 2000. In unsprayed and carbendazimsprayed whole plots, a stable coexistence of about 50% each of T. yallundae and T. acuformis developed within five seasons, but in whole plots sprayed with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…1). That the fungicide application regimen affects the sensitivity of a population has been shown for the powdery mildews of barley and cucurbits, the wheat eyespot fungus Pseudocercosporella herpotrichoides, and the apple scab fungus Venturia inaequalis (2,7,19,22).…”
mentioning
confidence: 99%
“…1). That the fungicide application regimen affects the sensitivity of a population has been shown for the powdery mildews of barley and cucurbits, the wheat eyespot fungus Pseudocercosporella herpotrichoides, and the apple scab fungus Venturia inaequalis (2,7,19,22).…”
mentioning
confidence: 99%
“…A prevalence of O. acuformis and restricted occurrence O. yallundae may be related to the common use of carbendazim for controlling eyespot (Bateman 2002;Bierman et al 2002;Birchmore et al 1992;Blein et al 2009;Dayer et al 1995;Głazek et al 1993;Korbas et al 1999;Smith et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Previously Leroux and Gredt (1997) found that o. yallundae and o. acuformis co-occurred on up to 56% of the stems in a survey of wheat crops in France. Bierman et al (2002) described a stable coexistence of about 50% of both species in unsprayed and carbendazim sprayed plots for five seasons in the UK.…”
Section: Discussionmentioning
confidence: 98%